Examining restricted and repetitive behaviors in young children with autism spectrum disorder during two observational contexts. (February 2014) - Stronach, Sheri; Wetherby, Amy M
This prospective study of the FIRST WORDS ® Project examined restricted and repetitive behaviors in a sample of 55 toddlers at a mean age of 20 months who were later diagnosed with autism spectrum disorder. Restricted and repetitive behaviors were coded using the Repetitive Movement and Restricted Interest Scales in two video-recorded observation methods–structured sampling procedures in a clinic and naturalistic everyday activities at home. Measures of restricted and repetitive behaviors were higher in the clinic setting than in the home observation, especially for behaviors involving object use. Repetitive movements with objects in the clinic predicted nonverbal developmental scores and Autism Diagnostic Observation Schedule social affect scores at later follow-up. In contrast, repetitive movements with objects at home significantly predicted later Autism Diagnostic Observation Schedule restricted and repetitive behaviors scores. These results support the utility of the Repetitive Movement and Restricted Interest Scales to detect restricted and repetitive behaviors in toddlers and suggest that observations of restricted and repetitive behaviors in clinic and home settings may provide unique and important diagnostic information for improving early detection of autism spectrum disorder.